2017 Twelfth International Conference on Ecological Vehicles and Renewable Energies (EVER) 2017
DOI: 10.1109/ever.2017.7935882
|View full text |Cite
|
Sign up to set email alerts
|

Impact of battery ageing on e-mobility energy efficiency

Abstract: Abstract-This paper focuses on energy efficiency degradation of two lithium-ion technologies, NMC (Nickel Manganese Cobalt) and LFP (Lithium Iron Phosphate), under accelerated calendar ageing tests. Results reveal the importance of considering battery ageing in the design phase of electric vehicles, not only for capacity but also for energy efficiency reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…Another interesting result is that efficiency is generally quite constant in medium DoD levels and it rapidly decreases with extreme values (full charge or full discharge). This result is quite characteristic of LFP cells and differs from that obtained in NMC (Nickel Manganese Cobalt) cells [8], where efficiency is continuously decreasing with DoD.…”
Section: B Cycle Efficiencycontrasting
confidence: 88%
See 1 more Smart Citation
“…Another interesting result is that efficiency is generally quite constant in medium DoD levels and it rapidly decreases with extreme values (full charge or full discharge). This result is quite characteristic of LFP cells and differs from that obtained in NMC (Nickel Manganese Cobalt) cells [8], where efficiency is continuously decreasing with DoD.…”
Section: B Cycle Efficiencycontrasting
confidence: 88%
“…In some previous works, we showed that the energy efficiency is modified by cell aging and that it would be important to consider not only the efficiency of fresh batteries but also the efficiency of aged batteries when comparing two technologies [8]. The degradation of the efficiency could be linked with the fade of capacity [9].…”
Section: Introductionmentioning
confidence: 99%
“…A study has also been conducted on the energy efficiency of electric vehicles [16]. The optimal battery SOC range for battery vehicles has been estimated by analyzing the relationship between battery energy efficiency and battery SOC range [17]. There has also been discussion of the energy efficiency of NiMH batteries as they are applied to grid frequency control at various discharge currents [18].…”
Section: Introductionmentioning
confidence: 99%